Frontiers in Healthy Cities Policy Impacts and Inclusive Governance - Chen, Jie; Zhou, Qian; Zhang, Ting (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This collection that is based on the Special Issue contains 37 high-quality, rigorously peer-reviewed, cutting-edge pieces of original research applying a multi-disciplinary academic approach to study how to improve environment quality and healthy living in contemporary and future urban environments. This multidisciplinary collection helps to disseminate and communicate scientific knowledge and impactful discoveries of how to make healthy cities available to researchers, academics, and the general public globally.